Dynamical barrier and isotope effects in the simplest substitution reaction via Walden inversion mechanism - Zhiqiang Zhao (Nature Portfolio, 2017)
The H+CH4substitution reaction is the simplest reaction occurring via the Walden inversion mechanism. Here, the authors perform a theoretical study of the reaction and uncover the important effect of the umbrella motion of the non-reacting methyl group on the reaction dynamics.